'An example to all of Christendom' – Crime and social control in the Danish Island Parish of Drejø c. 1700-1900. (July 2021) - Jensen, Nils Valdersdorf
Abstract: Using the case of the island Parish of Drejø, Denmark, this article examines historical crime on small islands and adds to our understanding of islands as criminological spaces. Building on an analysis of the typology of the crimes committed on the five small islands of Skarø, Drejø, Hjortø, Hjelmshoved and Birkholm primarily in the nineteenth century and a quantitative analysis of the number of children born out of wedlock in the seventeenth, eighteenth and nineteenth centuries on the same islands, it is argued that the geography of the islands in question intensified social control and affected their criminological profile. The article concludes that placing social control in the center of island life links research on island crime and ideas of island utopias. Highlights: Uses a Danish island parish to understand how island space frames moral norms. Analyses the typology of crime and rates of children born out of wedlock. Documents how islanders experienced geographically intensified social control. Identifies how islanders outs unwanted inhabitants. Adds to our understanding of island space and the life in small communities.